2019
DOI: 10.1038/s41391-019-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure–response analyses of abiraterone and its metabolites in real-world patients with metastatic castration-resistant prostate cancer

Abstract: Background Abiraterone acetate is an oral 17α-hydroxylase/C17,20-lyase (CYP17) inhibitor approved for the treatment of metastatic castration-resistant prostate cancer (mCPRC) patients. Previously, a prospective observational trial demonstrated a relationship between abiraterone trough concentrations (C min ) in plasma and treatment efficacy. The aim of our study was to investigate the exposure-response relationship of abiraterone and its metabolites, and to study if the proposed target for abiraterone of 8.4 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
5
22
1
Order By: Relevance
“…This threshold was later confirmed in a real-world patient cohort (n = 62, PFS 6.1 vs. 16.9 months, p = 0.033) [63]. Yet, at the standard dose of 1000 mg once daily (QD), 35% and 42% of patients, respectively, did not reach this target [62,63]. A prospective study (n = 32) demonstrated that 20 patients (63%) had at least one C min < 8.4 ng/mL with standard care [40]; however, when a light meal or snack was concomitantly taken with abiraterone, adequate exposure in 28 patients (87.5%) without additional toxicities was achieved [40].…”
Section: Abirateronementioning
confidence: 67%
See 1 more Smart Citation
“…This threshold was later confirmed in a real-world patient cohort (n = 62, PFS 6.1 vs. 16.9 months, p = 0.033) [63]. Yet, at the standard dose of 1000 mg once daily (QD), 35% and 42% of patients, respectively, did not reach this target [62,63]. A prospective study (n = 32) demonstrated that 20 patients (63%) had at least one C min < 8.4 ng/mL with standard care [40]; however, when a light meal or snack was concomitantly taken with abiraterone, adequate exposure in 28 patients (87.5%) without additional toxicities was achieved [40].…”
Section: Abirateronementioning
confidence: 67%
“…In an observational study in 61 metastatic castration-resistant prostate cancer patients, C min ≥ 8.4 ng/mL were associated with a significantly longer PFS compared to C min < 8.4 ng/ mL (PFS 7.4 vs 12.2 months, p = 0.044) [62]. This threshold was later confirmed in a real-world patient cohort (n = 62, PFS 6.1 vs. 16.9 months, p = 0.033) [63]. Yet, at the standard dose of 1000 mg once daily (QD), 35% and 42% of patients, respectively, did not reach this target [62,63].…”
Section: Abirateronementioning
confidence: 73%
“…Next to the biomarkers, we studied the effect of drug exposure on PFS. It has been suggested that underexposure of abiraterone ( C trough level < 8.4 ng·mL −1 ) is related to shorter PFS [26,27]. The beneficial effect of higher abiraterone exposure levels could not be confirmed in this study for chemotherapy naïve patients treated with AA‐P.…”
Section: Discussionmentioning
confidence: 63%
“…Nuland et al confirmed the exposure threshold in a real-life cohort of 62 mCRPC patients, in which 42% of the patients were chemotherapy-pretreated. Suprisingly, in the group of patients with an exposure below the threshold 65% of the patients were chemotherapy-pretreated versus 25% in the group of patients with an exposure above the threshold 9 . So it might be well possible that if both studies analysed the patients who received AA before or after chemotherapy in mCRPC setting independently, results would be consistent with our findings.…”
Section: Discussionmentioning
confidence: 90%
“…It was demonstrated that patients with primary resistance to AA had a significantly lower abiraterone exposure, compared to responders 8 . Furthermore, earlier studies in patients with mCRPC treated with AA showed that patients exposed to an abiraterone trough concentration (Cmin) above 8.4 ng/mL had an improved progression-free survival (PFS) compared to patients below this threshold 7,9 . This exposure threshold was thereafter proposed for all mCRPC patients treated with AA.…”
Section: Introductionmentioning
confidence: 99%